Hubungan Body Image Terhadap Harga Diri Siswi Kelas IX di MTsS Lam Ujong Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The teenage period is a crucial phase in developing self-esteem and body image, which play a significant role in shaping adolescent character. Adolescent girls often face social pressures related to physical appearance, which impacts on self-perception. This study aims to determine the correlation between body image and students’ self-esteem. The study was conducted at MTsS Lam Ujong, Krueng Barona Jaya District, Aceh Besar on May 05th, 2025. This study used a quantitative approach with an analytical descriptive design. The sample consisted of 53 students selected by using a total sampling technique. The instruments used were the Multidimensional Body Self Relations Questionnaire (MBRSQ) with Cronbach Alpha 0.774 and the Rosenberg Self-Esteem Scale (RSES) with Cronbach Alpha 0,877. The univariate and bivariate data analysis using the Pearson Chi-Square test. The results showed that most respondents with negative body image had low self-esteem (94.1%), while respondents with positive body image showed variations in self-esteem. The Chi-Square test indicated a p-value of 0.001 (p < 0.05), indicating a significant correlation between body image and self-esteem. These findings indicate a significant correlation between body image and students’ self-esteem. This study suggests that schools and counselling teachers provide psychosocial education and mentoring to help students build a positive body image.